Behavioral Economics, Motivating Psycho-Education Improvements: A Mobile Technology Initiative in South Africa - Forsythe, Alexandra Mary; Venter, Catherine (Frontiers in Psychology, 2019)
Here we report on a health behavioural support project, using incentivised behaviour on a mobile platform through M4JAM. This was a proof of concept study to support further developments, more specifically targeted at the management of Tuberculosis and Human Immunodeficiency Virus. The study reported here examines the impact of financial rewards and app towards improving mental health outcomes in South Africa. 136 participants were recruited from a database and dichotomized into self-determined and heteronomous groups based on self-report scores. Overall the findings highlighted that personal financial incentives have a role in motivating behaviour and that individuals with higher levels of self-determinate motivation. The findings are discussed in light of the usefulness of an incentivized mobile platform in real-world practice to encourage mental health improvements in a low to middle-income countries.